Four-Face Heated Uniaxial Reinforced Concrete Columns Interaction Charts - Mohammed S. Al-Ansari; Muhammad S. Afzal (Civil Engineering Journal, 2023)
This paper presents an analytical method for generating the interaction diagrams of uniaxially reinforced concrete (RC) columns that are subjected to four-face heating. Twenty-one (21) specimens obtained from previous case studies that were subjected to four-face heating (with different fire test times ranging from 63 to 356 fire minutes) are used to validate the proposed uniaxial interaction charts. The results obtained from the case studies and from the proposed charts are also compared with the finite element software (FIN EC). The 500°C isotherm as well as the zone method are used in the computer software program to find the required load capacities. The proposed method's values fall within the range of values obtained from laboratory tests and computer software, which suggests its validity. Also, the zone method in FIN-EC software is reliable for evaluating load-bearing capacity, while the 500°C method is useful in situations with shorter fire times. The results obtained provide a valuable tool for designing and evaluating structures that may be exposed to fire. Nonetheless, the study is restricted by its concentration on a particular type of column under four-face heating, which may reduce its relevance to other types of structures and heating situations. Doi: 10.28991/CEJ-2023-09-07-01 Full Text: PDF